Getting personal (London Hodder, 2006)
Why is it that your best friend always seems to end up with men who treat her badly? Why is that your best male friend seems intent on dating the kind of girl who thinks that Nietzche is an STD? Why is it that your own little black book looks more and more like the non-celeb client list of the Priory? Why can't any of you find someone quite right? Ruby, Martin and Lou are three old friends who have spent too much time talking about the ones that got away. Facing another summer without love, they decide to approach the dating dilemma in the way they approached finding flatmates. They're going to place personal ads. For one another.
Keywords: Mate selection -- Great Britain -- Fiction; Personals -- Great Britain -- Fiction